The development,validation and evaluation of Rusnani Concept Mapping (RCM) on academic performance of diploma nursing students / Rusnani Ab Latif - Ab Latif, Rusnani (2019)
In Malaysian nursing education, concept mapping is not widely practised among the nurse educators and the students. Concept mapping is an innovative teaching learning strategy requires a well-planned and developed concept mapping guideline to guide nurse educators to use the concept as a teaching strategy. Therefore, the researcher aims to develop and evaluate the effectiveness of the Rusnani Concept Mapping (RCM) on academic achievement and clinical practices among diploma of nursing students. The development of this RCM was based on Mohd Afifi Learning Model (MoAFF) and ADDIE Model integrated with the Kemp Model. RCM is a concept mapping guideline that developed by researcher and is validated with face and content validity and the Delphi techniques. The reliability of the RCM was .816. The study design is quasi-experimental with two groups. The experimental and control groups received education using RCM and lecture method respectively. Data were analyzed using descriptive and inferential statistic using independent t-test and paired t- test. P values less than 0.05 were interpreted as significant. In the pre-test, the students taught using RCM had achievement mean scores of 11.23 and SD=2.58, and a mean score of 13.19, SD=1.71 in the post-test with mean gain scores of 1.96 at p=. 0.01. In contrast, students taught using lecture method had a mean achievement scores of 10.71 and SD=2.23 in the pre-test and a mean score of 12.60, SD=1.64 in post-test achievement with mean gain scores of 1.89 at p=0.01. The post-test score of the experimental and control groups was significant (t=2.53, p=0.013). In students’ grade achievement, the results show an increase in post-test, the percentage pass for the experimental group increased from 95.4% in pre-test to 100% in the post-test. Meanwhile, in control group had increased from 93.57% in pre-test increased to 99.08% in the post-test. The mean concept mapping care plan scores for the experimental and control groups was 65.23, SD=9.28 and 59.33, SD=11.26 respectively with p=0.01. The result of students’ perception regarding concept mapping in experimental group showed as positive moderate with a mean score of 3.44. These findings showed that RCM was effective in promote critical thinking and increase academic performer among nursing students. This study provides additional evidence that RCM is instructionally valuable as a learning method and is an active learning strategy for meaningful learning and motivating superior achievement in students.